Math

Aus Wiki.csoft.at

(Unterschied zwischen Versionen)
(Siehe auch)
(Ergebnis)
Zeile 15: Zeile 15:
   
   
  <math>V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}</math>    <math>A_O = a^2\sqrt{3}</math>
  <math>V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}</math>    <math>A_O = a^2\sqrt{3}</math>
-
 
-
<math>\frac{1}{\pi} = (\frac{2}{9801})</math>
 
=Siehe auch=
=Siehe auch=

Version vom 15. Juni 2006, 07:01 Uhr

Inhaltsverzeichnis

Syntax

<math>(\bar{B} + \bar{A}) \cdot (\bar{D} + \bar{C} + A)</math>
<math>\pi = \frac{3}{4} \sqrt{3} + 24 \int_0^{1/4}{\sqrt{x-x^2}dx}</math>
<math>a^2-b^2 = (a+b) \cdot (a-b)</math>
<math>Z(\{x[n]\}) = X(z) := \sum_{n=-\infty}^{\infty}x(n)z^{-n}</math>

Ergebnis

 (\bar{B}+\bar{A})\cdot(\bar{D}+\bar{C}+A)


a^2-b^2 = (a+b) \cdot (a-b)

V = \frac{a^3\sqrt{2}}{12} = \frac{1}{6} \cdot \begin{vmatrix} x_1 & y_1 & z_1 \\ x_2 & y_2 & z_2 \\ x_3 & y_3 & z_3 \end{vmatrix}     A_O = a^2\sqrt{3}

Siehe auch

Weblinks